Persons With Advanced Alzheimer's Disease Engage in Mild Leg Exercise Supported by Technology-Aided Stimulation and Prompts. (January 2017) - Lancioni, Giulio E.; Singh, Nirbhay N.; O'Reilly, Mark F.; Sigafoos, Jeff; D'Amico, Fiora; Addante, Luigi M.; Pinto, Katia
This study assessed whether nine persons with advanced Alzheimer's disease would learn to engage in leg responses (exercise) with the support of a technology-aided program, which provided (a) preferred stimulation contingent on the leg responses and (b) verbal reminders/prompts in case of no responding. The study was conducted according to a non-concurrent multiple baseline design across participants and involved sessions of 5 min. During the baseline, the participants' mean frequencies of leg responses ranged from zero to slightly above two per session. During the intervention, those frequencies ranged from nearly 10 to nearly 17 per session. The mean frequencies of prompts varied across participants from about two to more than seven per session. In addition to the increase in leg responses, participants showed an increase in signs of positive personal involvement (e.g., smiles and positive verbalizations) during the intervention sessions as compared with the baseline sessions. The applicability and potential benefits of the program in daily contexts are discussed.